Analisis produk dan perancangan combination tool pada produk jam suvenir Polman Bandung - Budiarto, H. A.; Permana, S.; Erlangga, Y.Y.; Prabowo, H.A. (Universitas Mataram, 2022)
Product Based Education is an educational concept that integrate the educational curriculum with the industrial world. This learning help to improve the learning process and student skills by practices under industrial conditions. Moreover, it also improves the quality of teaching and increases the percentage of learning outcomes. Polman Bandung has developed a product called Polman Bandung souvenir clocks made of sheet metal to implement PBE. In this study, a product that has a Polman identity with engineering characteristics was produced and became a practicum media for students majoring in precision tool-making engineering at Polman Bandung. Verein Deutsche Inginieuer 2222 was used as a guideline so that the research carried out is clear, directed, and systematic. The focus of this research is to develop the product by using Autoform as a simulation software for metal forming. The design of the press tool is made based on the product analysis results. Forming analysis has been done to determine the feasibility, formability, and distribution of body component materials by using Autoform. The results showed that Aluminum 1050 sheet metal with 0.5 mm of thickness is suited for this product. The optimum free blank is 170 × 170 × 0.5 mm and feasible to make. The distribution of Forming Limit Diagram showed that the safe area is 68.5%, the insufficient stretch areas of 1.02%, the wrinkling areas tendency of 19.12%, and wrinkled areas that are still within the tolerance limit of 11.35%.